Effects of sulfur-fumigation on the pharmacokinetics, metabolites and analgesic activity of Radix Paeoniae Alba. (15th February 2018) - Kong, Ming; Liu, Huan-Huan; Wu, Jie; Shen, Ming-Qin; Wang, Zhi-Gang; Duan, Su-Min; Zhang, Yan-Bo; Zhu, He; Li, Song-Lin
Abstract: Ethnopharmacological relevance: Radix Paeoniae Alba ( Baishao, BS), one of the most commonly used traditional Chinese medicinal herbs, has many pharmacological effects including analgesic activity. Previous studies found that sulfur-fumigation, a post-harvest handling process developed to prevent mold contamination of medicinal herbs, altered the quality of BS. However, whether sulfur-fumigation affects the pharmacokinetics, safety and efficacy of BS warrants further investigation. Aim of the study: To evaluate the feasibility of sulfur-fumigation as a post-harvest handling process of BS from the viewpoints of pharmacokinetics, safety and efficacy. Materials and methods: The pharmacokinetic behaviors of four active components of BS and one characteristic component of sulfur-fumigated BS (S-BS) were evaluated by high performance liquid chromatography triple quadrupole mass spectrometry (HPLC-TQ-MS/MS). The safety was investigated using ultra high performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS/MS) based metabolomics approach after intragastric (i.g.) administration of non-fumigated BS (N-BS) and S-BS in rats. The analgesic efficacy was compared using hot-plate test in mice, after i.g. administration of N-BS and S-BS, at both high and low dosages. Results: Systemic exposures of paeoniflorin and oxypaeoniflorin, two analgesic components of BS, were significantly decreased in the S-BS treated group compared to the N-BS treated group, while paeoniflorin sulfonate, one of the sulfur-containing derivatives of S-BS, was detected in all time-points of S-BS treated group with the area under the plasma concentration–time curve (AUC0−t ) and the maximum plasma concentration (Cmax ) as high as 7077.06 ± 2232.97 ng/mL*h and 1641.42 ± 634.79 ng/mL respectively, which indicated that sulfur-fumigation altered the pharmacokinetic behaviors of BS. Besides, paeoniflorin sulfonate and its four metabolites with ambiguous toxicities, as well as one endogenous metabolite p-cresol glucuronide, the biomarker of disordered homeostasis of intestinal bacteria and bile acid, were identified as the characteristic metabolites in S-BS administered rats, suggesting that sulfur-fumigation reduced the safety of BS. Furthermore, the analgesic effects at both low and high dosages were decreased in different extent when compared to N-BS administered groups, indicating that sulfur-fumigation weakened the efficacy of BS. Conclusion: Sulfur-fumigation altered the pharmacokinetics, as well as reduced the safety and efficacy of BS, suggesting that sulfur-fumigation is not recommended for post-harvest handling of BS. Graphical abstract: